Investigating Current Academic Stress and Test Anxiety for Undergraduate Students Experiencing the Covid-19 Pandemic of 2020 - Heather Marie Manitzas Hill; Farwah Binte Alam; Deirdre Yeater (Journal of the Scholarship of Teaching and Learning, 2025)
Around the world, students of all ages are becoming increasingly stressed. Academic stress and test anxiety are two aspects of education-based stress that have been studied since the 1980s. Despite attempts to identify myriad predictors and to develop interventions that can mitigate these two educational impediments, undergraduate students continue to report high levels of stress. The current study was an opportunistic study that investigated the effect of the Coronavirus 2020 pandemic on academic stress and test anxiety among 200 undergraduate students at two primarily undergraduate institutions (PUIs) with different ethnic and SES compositions. The study also assessed the influence of the presence of a pet on reported academic stress and test anxiety levels. No difference was found between levels of academic stress or test anxiety for students evaluated before the pandemic began, when transitioning to a pandemic status, or during the pandemic with quarantine in effect. Moreover, the presence of a pet did not mediate the self-reported levels for either academic stress or test anxiety. However, academic stress and test anxiety levels were at an all-time high compared to previous cohorts assessed across multiple decades with females showing a greater vulnerability in both areas of stress. These results highlight the critical importance of identifying factors that are driving these stressors and developing effective interventions for undergraduate students to manage their stress levels.